Humic Matter in Soil and the Environment: Principles and Controversies - Tan, Kim H. (CRC Press, 2009)
This book tries to address the problem of complete coverage as highlighted above. In addition to its value as a textbook, it can be used equally well as a reference book by all interested in humic matter. The issues and controversies associated with humic acids are analyzed from the two different viewpoints mentioned above. The advances of the past century, and the prospects for advancing humic acid science in the new millennium, are explored from both viewpoints. The text also carries a message for increasing awareness of the appearance of more and more data, emphasizing the ubiquitous presence of humic compounds in nature and their impact on the environment, soils, and agriculture. The intensified application of humic substances in industrial and pharmaceutical operations is discussed, underscoring the significance of humic acids as highly important organic substances in nature. The production and use of therapeutic chemicals from humic acids and the manufacture of commercial humates for use in soils, which has grown lately into a multimillion dollar business, are addressed. These are issues of considerable interest to people studying, practicing, and producing medicines and fertilizers, and therefore enlarges the audience for this book beyond the scope of soil, agricultural, and chemical science.